A study of prevalence of anemia and associated risk factors in pregnant women of tribal community attending antenatal clinic at Trivandrum district, Kerala, India - Ponny, M. S.; Nandini, V. R.; Nirmala, C.; Mayadevi, Brahmanandan (International Journal Of Community Medicine And Public Health, 2021)
Background: Anemia is a major preventable public health concern among the pregnant women worldwide. The present study aims at determining the prevalence of anemia among tribal pregnant women at Trivandrum district, Kerala and identifying its socioeconomic and gynaecological risk factors. Methods: A cross sectional study was conducted among tribal women attending antenatal clinics of Vithura and Kuttichal Government hospitals at Kerala, India. Sample size was calculated as 117. All consecutive subjects fitting the inclusion criteria were included in the study until the sample size was achieved. Patients were interviewed using a semi structured questionnaire which includes socio demographic, cultural and nutritional factors. Hemoglobin measurement was done while first antenatal visit using semi auto hemo-analyzer. Data obtained were analyzed using SPSS software. Statistical test used was either Chi-square test or student t-test. Results: The prevalence of anemia among the tribal pregnant women attending primary health care in Trivandrum during the study tenure was 53.33%. The prevalence of mild, moderate and severe anemia was observed as 26.66%, 25% and 1.66% respectively. The mean serum haemoglobin level among the study group was found to be 10.64 gm%. The major risk factors associated with anemia were figured out to be low body mass index, low family income, high parity, joint family, exposure to passive smoking and pan chewing, irregular intake of iron and folic acid supplements, hyperemesis and absence of deworming. Conclusions: Focus shall be given on creating awareness among tribal women regarding the need for dietary and lifestyle modification to decrease the prevalence of anemia among them.